Influence of Parents and School Environment on Student Learning Interest of Class XI Students of the Network Computer Engineering School in Learning PPKN in SMK Negeri 1 Solok Selatan - Novi Riani; Ranti Nazmi; Budi Juliardi (CV. Rayyan Dwi Bharata, 2023)
Improving the quality of education is one of the main learning objectives so that several efforts are needed to change the position of the quality of education, one of which is by looking at the influence of parents and the school environment. This study aims to determine the effect of parents on interest in learning, and the school environment on the interest in learning of class XI students majoring in Network Computer Engineering for the 2021/2022 academic year. The research method used in this research is descriptive quantitative, with the research location at SMK Negeri 1 Solok Selatan. With the subject of parents, and students. The data collection used is observation, questionnaire distribution, and documentation. The accuracy of the data was tested using data analysis techniques starting with questionnaire collection, normality test, multicollinearity test, multivariate regression analysis, coefficient of determination (R2), t-test (partial) and F-test (simultaneous). Based on the research results obtained from the t test, it can be concluded that the variable (1) parental influence, has a positive and significant effect on the interest in learning of class XI students majoring in network computer engineering at SMK Negeri 1 Solok Selatan , seen from the coefficient value of 0.047, this figure is positive and significant to the interest in learning of class XI students majoring in network computer engineering at SMK Negeri 1 Solok Selatan in the 2021/2022 academic year. (2) The school environment has a positive and significant effect on the learning interest of class XI students majoring in network computer engineering at SMK Negeri 1 Solok Selatan, seen from the coefficient value of 0.038, this figure is positive and significant to the learning interest of class XI students majoring in network computer engineering at SMK Negeri 1 Solok Selatan in the 2021/2022 academic year. Based on the results of the study, it can be concluded that there is an influence between the variables of parental influence and school environment on student interest in learning with an Fcount value of 4.730 Ftable 3.34 and a significant value of 0.018 Î± = 0.05 , this means that H0 is rejected and Ha, thus it can be said that the influence of parents and the school environment is significant in the learning interest of class XI students majoring in network computer engineering in the 2021/2022 academic year.